2000
DOI: 10.1021/jf0002544
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Furylfuramide-Induced SOS Response by Monoterpenoids with a p-Menthane Skeleton Using the Salmonella typhimurium TA1535/pSK1002 Umu Test

Abstract: Suppression of the furylfuramide-induced SOS response by 25 kinds monoterpenoids (hydrocarbons, alcohols, ketones, and aldehydes) with a p-menthane skeleton was studied. Suppression of the SOS-inducing activity by monoterpenoids was determined in the umu test using Salmonella typhimurium TA1535/pSK1002. The terpene alcohols, ketones, and aldehydes had potent suppressive effects, but the hydrocarbons did not. Especially, (+)-menthol, (+)-pulegone, piperitenone, and cuminaldehyde were shown to have the most pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The other compounds present in these extracts, such as tannins, saponins, and terpenes, have been described as nonmutagenic or antimutagenic [Deguchi et al, 2000;Berhow et al, 2000;Miyazawa et al, 2000]. It appears that the opposite properties of flavonoids are due to a structureactivity relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The other compounds present in these extracts, such as tannins, saponins, and terpenes, have been described as nonmutagenic or antimutagenic [Deguchi et al, 2000;Berhow et al, 2000;Miyazawa et al, 2000]. It appears that the opposite properties of flavonoids are due to a structureactivity relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that patchouli oil has a variety of pharmacological activities, including antiemetic (4), anti-inflammatory (3,5), anti-allergic (6), immunomodulatory (7) and antimicrobial actions (8). chemically, it has been reported that Pogostemon cablin contains sesquiterpenes (9), cytotoxic chalcones (10) and antimutagenic flavones (11). Patchouli alcohol (PA; chemical structure in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Miyazawa et al have previously reported a suppressive effect against the chemical mutagen-induced SOS response of monoterpenes with a six-membered ring containing an ,-unsaturated ketone group (e.g., piperitenone and (þ/À)-carvone) and isofraxinellone with a lactone moiety. 15,16) These findings indicate that an ,-unsaturated ketone or a lactone group was also essential for the observed biological activity. The structureactivity relationship seems to be in good agreement with our results.…”
Section: Resultsmentioning
confidence: 77%
“…GNL, GN 2 L and GN 3 L were found to possess strong suppressive effects in the range of 43-54% at a concentration of 400 mM. The inhibition by GN n L was 2 to 2.5-fold greater than that by (À)-carvone 15) which is a well-known inhibitor of the AF-2-induced SOS response ( Table 1). The suppressive effect of GN 3 L increased in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 96%